Formation of professional motivation of students in the study of the course of Faculty Surgery - Klimenko, V. M.; Zakharchuk, O. V.; Zakharchuk, O. V.; Vakulenko, V. V.; Dosaieva, A. S. (Zaporozhye Medical Journal, 2014)
The discussion about the necessary shift from teaching to learning has been considerably boosted by the Bologna Process and related issues such as qualification frameworks, the European Credit Accumulation and Transfer System (ECTS) and the Diploma Supplement. Teaching and learning in higher education is a shared process, with responsibilities on both student and teacher to contribute to their success. Within this shared process, higher education must engage students in questioning their preconceived ideas and their models of how the world works, so that they can reach a higher level of understanding. Nobody would contest that we need high quality teaching and learning throughout our education and training systems. The aim of this work was to examine the effect of student scientific circle of Surgery on the formation of professional motivation of students. An important form of scientific-research work of students in Zaporizhia state medical university (ZSMU) is functioning of student’s scientific circle as branche of Scientific Student Association. In task group are also practical skills, which is primarily important for, the formation of a future doctor character qualities such as tenacity, ambition, determination. The feature of the circle is that students study discipline independently, using help of the department teachers, collaborate with students of other scientific circle and societies of ZSMU and other Ukraine medical high schools. The best teaching helps students to motivates them to learn. The results of monitoring in 2012-2013 showed that about 85% of students improved learning outcomes from such disciplines as operative surgery and topographic anatomy, propaedeutic Internal Medicine, General Surgery, Faculty surgery, Hospital surgery. Presented the possibilities of using various forms information technology to enhance learning, acquire new knowledge and information sharing. Every year students of surgery circle participate in student conferences with international participation, receive prizes. Teaching and learning are fundamental core missions of university, that involve students in governance, curricular design, development and review, quality assurance and review of the procedures. Academic staffs are employed not just to teach, but to teach on a high professional level. Thus, student scientific circle is an important means to improve the efficiency of education contributes to future surgeon.